ELECTRIC VEHICLE PROPELLED BY DUAL-INDUCTION MOTORS STRUCTURE: EXPERIMENTAL RESULTS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
An electric vehicle (EV) is an adaptation of a conventional vehicle with the integration of electrical motors. It is one of the most promising technologies that can significantly improve vehicle performance and polluting emissions. The drive association's many EV configurations and possibilities can be envisaged according to EV performances, weight, and cost. This paper presents the experimental validation of an electric differential speed action resulting from the proposed structure of an electric vehicle using dual-induction motors vector controlled, placed at the rear wheels operating at a different speed. This controls the vehicle speed of the left and right wheels during steering maneuvers. For this purpose, to perform this experimental validation and prove the main functionalities of the proposed structure, a test bench was implemented containing an actual laboratory motor placed in the left rear wheel and a motor simulation model for the right one. The outcomes show that the experimental results confirm the validity and usefulness of the proposed propulsion structure.
Keywords: Electric vehicle (EV); Electric differential; Induction motor; Propulsion structure; Vector control